Alterações nos atributos edáficos, nos estoques de carbono e nitrogênio e nas frações da matéria orgânica após substituição da vegetação natural por pastagens na Amazônia maranhense - Rego , Carlos Augusto Rocha de Moraes (2021)
The conversion of native areas for exploitation with extensive beef cattle is common in Brazil. In the state of Maranhão, due to the low technological level of the producers, the use of fire to prepare the areas and the edaphoclimatic characteristics have suffered harmful changes to the edaphic environment. This study aimed to evaluate the changes in chemical, physical, biological attributes and the forms of carbon (C) and nitrogen (N) in the soil in Argiluvic Plintosol in the region of Amazônia Maranhense, caused by the replacement of natural vegetation by grasslands and the recovery of these with different. The following managements were assessed: Secondary Forest (SF), Grassland (PP), Grassland recovered and formed five years ago by the intercropping of corn + Brachiaria brizantha cv. Marandu (P5) and Grassland recovered and formed eight years ago by the intercropping of corn + Brachiaria brizantha cv. Marandu (P8). The variables evaluated were the physical attributes: soil density (Ds), total porosity (Pt), macroporosity (Ma), microporosity (Mi), penetration resistance (Rp) and soil moisture (Ug); the biological attributes: C content of microbial biomass, basal respiration, metabolic quotient and microbial quotient), and chemical attributes: pH, H+Al, Al3+, P, K+, Ca2+, Mg2+, OM, SB, CTC, V, carbon total organic matter (TOC), total nitrogen (TN), stocks of C and N, carbon and elemental nitrogen (CT and NT), abundance of δ13C and δ15N isotopes, oxidizable fractions (F1, F2, F3 and F4), humic substances (fulvic acids, humic acids, humin), granulometric physical fractions (particulate C and N (POC and PON) and associated with minerals (AMOC and AMON)) and the carbon management index (CMI) in the layers of 0.000.10, 0.10-0.20, 0.20-0.30 and 0.30-0.40 m. The FS and P8 areas showed the greatest contributions of the surface layer on the OM contents and together with the PP on the soil sorption complex. For the physical and biological attributes, the FS and P8 areas provided positive impacts in the improvement of these parameters. The replacement of the secondary forest for an environment of perennial grassland resulted in alterations of the C and N contents of the soil, granulometric fractions of SOM and CMI. The highest C contents of the humic substances were observed in the FS on the surface, as well as in the areas P8 and P5, while in depth the areas P8 and P5 present the greatest contributions. In relation to the oxidizable fractions, the greatest contributions within the F1 and F3 fractions were verified in the P8 area, differing from the others, in part of the analyzed layers. Along the profile, the P8 area showed the highest levels of total C and N. Regarding C and N stocks, it was observed that the P8 and PP areas presented the highest values when compared to FS. Due to the natural abundance of δ13C, it was possible to observe the highest enrichment in the PP area, P5 and P8 intermediate behavior and in the FS the lowest enrichment, while for δ15N there were no differences. Grassland recovery eight years ago showed better results than perennial grassland and forest, contributing to the capacity to improve soil C and N storage, with better results on soil attributes provided by the characteristics inherent to the root system of the plants forages Brachiaria brizantha cv. Marandu.